Take the money and run? Redemption of a gift card incentive in a clinician survey. Issue 1 (December 2016) - Chen, Jane; Sprague, Brian; Klabunde, Carrie; Tosteson, Anna; Bitton, Asaf; Onega, Tracy; MacLean, Charles; Harris, Kimberly; Schapira, Marilyn; Haas, Jennifer
Abstract Background Clinician surveys provide critical information about many facets of health care, but are often challenging to implement. Our objective was to assess use by participants and non-participants of a prepaid gift card incentive that could be later reclaimed by the researchers if unused. Methods Clinicians were recruited to participate in a mailed or online survey as part of a study to characterize women's primary health care provider attitudes towards breast and cervical cancer screening guidelines and practices (n = 177). An up-front incentive of a 50 gift card to a popular online retailer was included with the study invitation. Clinicians were informed that the gift card would expire if it went unused after 4 months. Outcome measures included use of gift cards by participants and non-participants and comparison of hypothetical costs of different incentive strategies. Results 63.5 % of clinicians who responded to the survey used the gift card, and only one provider who didn't participate used the gift card (1.6 %). Many of those who participated did not redeem their gift cards (36.5 % of respondents). The price of the incentives actually claimed totaled 3700, which was less than half of the initial outlay. Since some of the respondents did not redeem their gift cards, the cost of incentives was less than it might have been if we had provided a conditional incentive of 50 to responders after they had completed the survey. Conclusions Redeemable online gift card codes may provide an effective way to motivate clinicians to participate in surveys.